Global gender constitutionalism and women's citizenship a struggle for transformative inclusion - Rubio-Marín, Ruth (Cambridge, United Kingdom Cambridge University Press, 2022)
Constitutions around the world have overwhelmingly been the creation of men, but this book asks how far constitutions have affirmed the equal citizenship status of women or failed to do so. Using a wealth of examples from around the world, Ruth Rubio-Marín considers constitutionalism from its inception to the present day and places current debates in their vital historical context. Rubio-Marín adopts an inclusive concept of gender and sexuality, and discusses the constitutional gender order as it has been shaped by debates such those around same-sex marriage and the rights of trans persons. Covering a wide range of themes, from reproductive rights to political gender quotas and violence against women, this book offers a comprehensive feminist account of constitutional law. Truly international in scope and ambitious in subject matter, this is an invaluable resource for students and scholars working on gender within multiple disciplines.
Introduction : The when, why, what, and how of the book and how the personal becomes political -- 1 The constitutional establishment of the gender order : revolutionary times and exclusionary constitutionalism -- 2 Inclusive constitutionalism and its limits -- 3 Participatory constitutionalism : women as norm creators broadening the agenda -- 4 Transformative gender constitutionalism : toward an egalitarian family structure -- 5 Toward a constitutional gender erasure or a constitutional gender reaffirmation? -- Conclusion -- Index.
Includes bibliographical references and index.
Keywords: Women's rights; Constitutional law -- Social aspects; Law and globalization